Quantum Key Relay Scheme Based on Trusted Control Center - Shaosheng Jiang; Ruinan Chi; Xiaojun Wen (Dianxin kexue)
A transmit quantum key relay scheme based on trusted control center and trusted quantum relay server was proposed.The quantum key one-time pad encryption algorithm was used in the design of trusted relay protocol.Upon the establishment of trusted relay network,the trusted control center was used to ensure the credibility and security of access relay,and the user's IP address was hidden in the quantum information data that had been encrypted only for the legal user to decrypt and transmit credible information.The security analysis shows,users who do not connect with the quantum channel can still use the trusted relay network to transmit quantum key securely in a long-distance transmission while attackers can not obtain useful quantum key information from the network.